The taper: physiology, performance and planing - Pyne, D. B.; Mujika, I. (World book of swimming: From science to performance, 2012)
The taper forms the final part of the swimming training program prior to a major competition. The aim of the taper is to enhance competitive performance by reducing the degree of residual fatigue and optimizing physiological and psychological capacities. Various studies have reported cardiorespiratory, metabolic, hormonal, and neuromuscular changes during the taper. The expected mean improvement in competitive swimming performance with an effective taper is -0.3-5% although individuals will respond differently. The three primary types of taper are the linear taper (systematic reduction in training volume and load), exponential taper (with either a fast or slow decay), and the step taper (substantial standardized reduction in training volume and load). Training frequency is maintained or only a modest reduction of one or two training sessions per week should be made by the end of the taper. The intensity of training in main sets is held relatively constant. The typical reduction in training volume is -50-75% of the peak volume achieved during the training season. Tapers should be individualized according to the specific circumstances of swimmers (e.g. time required for elimination of residual fatigue and optimization of adaptations).